Medial Pancreatectomy for a Neuroendocrine Tumor Invading the Splenic Artery and Vein - Ait-Ali, Abdelmounaim; Sall, Ibrahima; El-Kaoui, Hakim; Bouchentouf, Sidi Mohammed; El-Hjouji, Abderrahmane; Rouibaa, Fadwa; Benkirane, Ahmed; Bounaim, Ahmed; Zentar, Aziz; Sair, Khalid (JOP. Journal of the Pancreas, 2016)
Context Pancreatic tumors in the midportion have traditionally been treated by an extended right or left pancreatectomy. A medial or central pancreatectomy is an alternative technique for benign or low-grade malignant neoplasms located to the left of the gastroduodenal artery and close to the splenomesenteric confluence. Case report A 38-year-old woman with no previous surgical history presented with epigastric abdominal pain. A computed tomography scan showed a 4 cm heterogeneous lesion within the pancreatic body. This tumor invaded the splenic artery and vein. There was no postoperative diabetes mellitus or exocrine insufficiency. The patient continues to be well after a 10-month follow-up without pancreatic insufficiency or local recurrence, and CT has demonstrated splenic perfusion by the collateral vessels. Conclusion We believe that a medial or central pancreatectomy may be a safe procedure where there is involvement of the large splenic vessels by a low grade malignant pancreatic tumor and that a systematic splenectomy is not justified. Image: Proximal pancreas and jejunal Roux-en-Y pancreaticojejunostomy.